ANALISIS YURIDIS TENTANG PENYALAHGUNAAN PEMBERIAN KUASA MENJUAL DALAM PERKARA PERDATA : STUDI KASUS PUTUSAN MAHKAMAH AGUNG NO.333K/PDT/2011 - SEVENTYN ARIANI ZAI (PREMISE LAW JURNAL, 2017)
Authorizarion is an agreement in which a person give an authority to someone else, on behalf of him, to do something. In the Civil Case No. 333K/PDT/2011, the plaintiffs argue that the defendants have commited illegal act because there is the misuse of authorization to sell committed by the defendants. The result of the research showed that the claim brought into the court by the plaintiffs because of the misuse of the Power of Attorney which was actually the authorization to sell but the defendants used it for making a cooperation agreement with another party to build housing on plaintiffs’ land. Each of the panel of judges had their own consideration respectively. Concerning Nemo Phis Yuris principle, the action of the receiver of the authorization was contrary to this principle. If there were other Power of Attorneys as what had been formulated by the defendants, the certificates should have been put in an addendum. Keywords: Authorization to Sell, Misuse of Authorization, Giving Authorization